Copper ferrite nanoparticles anchored laser-induced graphene as novel nanoenzyme for the electrochemical catalyzing and sensing of β-estradiol in serum - Cai, Minghui; Yao, Haixu; Li, Mengnan; Yan, Yan; Cao, Yang; Li, Jiaxin; Su, Huiyu; Zhang, Wenwen; Zhu, Hui; Cui, Feiyun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•We use copper ferrite nanoparticles and laser-induced graphene to modify SPCE.•This innovative biosensor can detect β-E2 in rats serum samples.•This sensor provides a new strategy for non-enzymatic β-E2 sensing.•This sensor may help to diagnosis and monitor female reproductive diseases. β-estradiol is one of the most active hormones in steroids, and it plays a vital role in the human reproductive and non-reproductive systems. Compared with other methods for detecting β-estradiol, electrochemical biosensors are economical, simple, sensitive, and rapid. Herein, spinel copper ferrite nanoparticles and laser-induced graphene (LIG) were employed to functionalize screen-printed carbon electrodes (SPCE) for the first time, and it demonstrated that they have a synergistic effect on the catalysis of β-estradiol. Differential pulse voltammetry (DPV) was used to detect the changes in the peak current generated by the oxidation of β-estradiol. The nanoparticles were characterized by Fourier infrared spectroscopy, transmission electron microscope, scanning electron microscopy, X-ray photoelectron spectroscopy (XPS), and X-ray Diffraction (XRD), and the composition elements and morphology of the nanoparticles were explained. The linear range of β-estradiol detected by this method is 0.1 ∼ 100 μM, R2 = 0.9992, and the detection limit is 3 nM. The sensor has good selectivity, reproducibility, repeatability, stability, and anti-interference performance. In rat serum, the recovery of the sensor at 100, 10, and 1 μM β-estradiol was 105 % ∼ 110 %, with relative standard deviations of 2.3 % ∼ 4.0 % (N = 3). This study shows that the sensor can be applied to detect actual samples and has potential application value for female reproductive-related diseases.